Edukasi Literasi Digital Marketing Bagi Pelaku UMKM di Pasar Sentral Medan - Irma Christiana; Chinta Felsya Fransisca; Alyssia Putri Manurung; Septia Mayang Saputri; Diah Ayu Zahra (Abdimas Universal, 2024)
The aim of this activity is to enhance knowledge and skills in digital marketing and e-commerce for micro, small and medium enterprises in an effort to increase their sales and profits. The methods used in this activity include: explanations, sharing and discussion experiences, as well as direct practice of creating a Shopee account and how to make it attractive to buyers. The object is the "Pulungan Fashion" store located on the 2nd floor kiosks No. 508–509 of the Central Market of Medan. The results showed that MSMEs perpetrators never used digital marketing because of a lack of technological skills. However, they showed great interest in using digital marketing and e-commerce sustainably.